StMADS11 Subfamily Gene PfMADS16 From Polypogon fugax Regulates Early Flowering and Seed Development - Zhou, Feng-Yan; Yu, Qin; Zhang, Yong; Yao, Chuan-Chun; Han, Yun-Jing (Frontiers in Plant Science, 2020)
The evolution of herbicide resistance in weedy plants leads to various adaptation traits including flowering time and seed germination. In our previous studies, we found an association of the early flowering phenotype with the ACCase inhibitor herbicide resistance genotype in a population of Polypogon fugax. MADS-box transcription factors are known to play pivotal roles in regulating plant flowering time. In this study, a SHORT VEGETATIVE PHASE (SVP)-like gene, belonging to the StMADS11 subfamily in the MADS-box family, was cloned from the early flowering P. fugax population (referred to as PfMADS16) and resistant to the herbicide clodinafop- propargyl. Overexpression of the SVP-like gene PfMADS16 in Arabidopsis thaliana resulted in early flowering and seed abortion. This is consistent with the phenotypic characters of resistant P. fugax plants, but contrary to the conventional role of SVP-like genes that usually suppress flowering. In addition, down regulation of the seed formation gene AtKTN1 in flowers of PfMADS16 transgenic Arabidopsis plants indicates that PfMADS16 may be indirectly associated with seed viability. Furthermore, one protein (PfMADS2) from the APETALA1 (AP1) subfamily interacting with PfMADS16 in P. fugax was identified with relevance to flowering time regulation. These results suggest that the PfMADS16 gene is an early flowering regulation gene associated with seed formation and viability in resistant P. fugax population. Our study provides potential application of PfMADS16 for integrated weed management (such as genetic-based weed control strategies) aiming to reduce the soil weed seedbank.